Is It Time to Let go of the Past? Effect of Clean Slate Regulation on Employment and Earnings - Kabir Dasgupta; Keshar Ghimire; Alexander Plum (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2021)
We focus on New Zealand's clean slate legislation to analyze whether automatic concealment of criminal records improves ex-offenders' labor market outcomes. Based on the legislation's eligibility requirements, we utilize detailed court charges information to identify comparable groups of ex-convicts who are subsequently linked to a population-wide tax register that documents monthly employment information. We use a difference-indifferences framework to compare clean slate-eligible individuals to former convicts who are approaching eligibility. Our analysis reveals that the clean slate scheme has no statistically relevant impact on employment propensity. However, we find a significant 2-2.5% increase in monthly wages during the post-implementation period.
Keywords: C21; J08; K14; 330; Clean Slate; Court Charges data; Monthly Tax Records; Conviction; Employment; Earnings; Difference-in-Differences; Tripledifference